PERSONIFICATION OF THE RISK OF HYPOXIC-ISCHEMIC BRAIN INJURY IN THE SYSTEM OF NEUROLOGICAL MONITORING OF CARDIAC SURGERY PATIENTS - Mankovskiy, D.S. (World of Medicine and Biology, 2021)
The study aimed to develop a screening algorithm for assessing the personalized risk of hypoxic-ischemic brain injuries in the preoperative period of cardiac surgery using artificial circulation. A comparative analysis of the frequency, prognostic value and diagnostic value of 26 clinical and anamnestic factors was performed in two groups of patients formed by the method of paired-comparison: 340 people with and 340 people without hypoxic-ischemic brain injuries. The most prognostically valuable factors were identified: the presence of manifestations of encephalopathy in the preoperative period – in 62.4 %, arterial hypertension – in 57.9 %, a history of closed traumatic brain injury – in 46.5 %, disorders of cerebral autoregulation – in 33.5 %, comorbid diabetes mellitus – in 34.2 %, a decrease in the left ventricular ejection fraction less than 30.0 % – in 23.7 %, and others. Prognostically unfavorable syndromes were identified and the screening tabular algorithm of risk personification of hypoxic-ischemic brain injuries based on risk assessments was substantiated.
Keywords: neurological monitoring; cardiac surgery; risk assessment; cerebrovascular disorders